Clinical Parameter for Deciding the BRAFV600E Mutation Test in Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance Thyroid Nodules: US Features According to TIRADS. Issue 4 (December 2017) - Rho, Miribi; Kim, Eun-Kyung; Moon, Hee Jung; Yoon, Jung Hyun; Park, Vivian Y.; Han, Kyunghwa; Kwak, Jin Young
Abstract : Abstract: This study aimed to investigate the usefulness of a thyroid imaging reporting and data system (TIRADS) to select thyroid nodules with atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) cytology for additional BRAF V600E mutation testing. Three hundred three thyroid nodules were included. Statistical analysis was performed at both patient and nodule levels according to BRAF V600E mutation positivity and clinical factors. Univariate and multivariate logistic regression analyses were performed to assess independent associations between BRAF V600E mutation positivity and clinical factors. Of 303 AUS/FLUS nodules, 16 (5.3%) of 303 nodules had the BRAF V600E mutation. The frequency of the BRAF V600E mutation according to the TIRADS was 35.7% for category 5, 10.8% for category 4c, 2.5% for category 4b, 1.1% for category 4a, and 0% for category 3 nodules ( P < 0.001). On multivariate analysis, BRAF V600E mutation positivity was significantly associated with high suspicion on the TIRADS (odds ratio, 15.247; P < 0.001). In conclusion, the ultrasonography patterns of the TIRADS can be used as a clinical parameter for deciding the BRAF V600E mutation test in thyroid nodules with AUS/FLUS cytology.